Technical Debt on Agile Projects: Managers point of view at Stack Exchange - Santos, Eder Pereira; Gomes, Felipe; Freire, Sávio; Mendonça, Manoel; Mendes, Thiago Souto; Spínola, Rodrigo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Context: The literature has proposed different approaches for Agile software development technical debt (ASD-TD) management, they are usually based on the point of view of software developers. Little is known about how project management practitioners actually perceive ASD-TD. Goal: To investigate how managers commonly discuss, experience, and manage ASD-TD, as well as roles, artifacts, and practices affected by ASD-TD extracted from Stack Exchange Project Management (SEPM). Method: We compiled 79 ASD-TD discussions from SEPM, and analyzed them quantitatively and qualitatively. Results: We identified 51 indicators used by managers to recognize ASD-TD items. The most commonly discussed types of TD are process and people debt. In addition, the Product Owner and Development Team are the most important roles with respect to ASD-TD. Sprint Backlog and Sprint Planning are the agile elements most affected by ASD-TD. We organized the TD indicators, roles involved, and agile elements affected by ASD-TD into a Mind Map. Conclusion: The perspective considered by project management practitioners to analyze the ASD-TD phenomenon is different from the one considered by other roles in agile software development.